Limitations of Using Administratively Reported Immunization Data for Monitoring Routine Immunization System Performance in Nigeria. (1st November 2014) - Dunkle, Stacie E.; Wallace, Aaron S.; MacNeil, Adam; Mustafa, Mahmud; Gasasira, Alex; Ali, Daniel; Elmousaad, Hashim; Mahoney, Frank; Sandhu, Hardeep S.
Abstract : Background. Efforts are underway to strengthen Nigeria's routine immunization system, yet measuring impact poses a challenge. We document limitations in using administrative data from 12 states in Nigeria and explore alternative approaches. Methods. We compared state-reported coverage with the third dose of diphtheria-tetanus-pertussis vaccine (DTP3) to district-reported coverage and data from coverage surveys conducted during 2006–2013. We used district-reported data during 2010–2013 to calculate the annual change in immunization coverage, the percentage of the target population that was unimmunized, and the number of vaccine doses administered. Data quality indicators were also assessed. Results. State-reported DTP3 coverage was 66%–102% in 2010, 49%–98% in 2011, 38%–84% in 2012, and 75%–123% in 2013 and was a median 46%–114% greater than survey coverage during 2006–2013. The mean local government area (LGA)–reported coverage varied substantially (standard deviation range, 10%–33% across years). For 2010–2013, the mean annual percentage change in LGA-reported DTP3 coverage was −15% from 2010 to 2011, −9% from 2011 to 2012, and 74% from 2012 to 2013; the mean annual percentage change in the percentage of the target population unimmunized was −62%, 426%, and −62%, respectively; and the mean annual percentage change in the number of doses administered was −13%, −7%, and 90%, respectively. Annually, a mean 14% of LGAs reported DTP3 coverage of >100%. Discussion. Assessing immunization system performance by using administrative data has notable limitations. In addition to long-term improvements in administrative data management, alternatives for measuring routine immunization performance should be considered.